Antiarthritic efficacy of Clematis orientalis (Bangladesh Journal of Pharmacology, 2018)
Clematis orientalis has been used traditionally to cure rheumatism, but its efficacy has not been scientifically explored in treating rheumatoid arthritis. The present study was designed to investigate the antiarthritic efficacy of C. orientalis using blockade of heat-induced protein alterations and HRBC membrane stabilization methods along with formaldehyde induced arthritis in rats. Aqueous ethanol (30:70) extract and various fractions (hexane, n-butanol and aqueous) produced concentration-dependent and significant (p